Doped nickel oxide-based material, preparation method and application thereof
By doping metal iron and sulfur atoms, efficient doped nickel oxide-based materials are prepared, which solves the problems of instability in active sites and low conductivity of nickel oxide materials, and achieves efficient electrolytic performance under alkaline conditions, and has wide application prospects.
Patent Information
- Application Number
- CN202411767103.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-04
- Publication Date
- 2025-03-07
AI Technical Summary
The active sites of existing nickel oxide materials are unstable during the electrolysis process, have low catalytic activity and low conductivity, which limits their application under alkaline conditions.
By doping metal iron and non-metal sulfur atoms, the electronic and structural properties of nickel oxide are changed to prepare efficient doped nickel oxide-based materials. The preparation method of the material includes using nickel nitrate and iron nitrate as nickel and iron sources, and after a series of stirring, heating, calcining and thiourea modification steps, a doped nickel oxide-based material with improved conductivity and stable active sites is finally obtained.
Doped nickel oxide-based materials exhibit excellent electrolytic properties under alkaline conditions, improve conductivity and catalytic activity, extend the service life of the electrode material, and reduce production costs.
Smart Images

Figure CN119571380A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of materials for electrolyzing water under alkaline conditions, and in particular to a doped nickel oxide-based material and a preparation method thereof. Background Art
[0002] In response to the increasingly serious energy shortage and environmental pollution, great efforts have been made to develop various eco-friendly energy storage / conversion systems, such as recyclable water electrolysis, sustainable carbon dioxide reduction reaction, and rechargeable metal-air batteries. However, the anodic oxygen evolution reaction (OER) of these systems involves a complex and slow multi-electron reaction process (4OH - =O 2 +2H 2 O+4e - ), which affects the reaction activity of the entire water electrolysis system. 2 and RuO 2 , which are considered to be one of the best performing OER electrocatalysts. Nevertheless, their scarce reserves and high prices have seriously hindered their large-scale industrial application. Therefore, it is very necessary to develop cost-effective OER catalysts with high activity and strong stability. Non-precious transition metal oxides, especially oxides of nickel, cobalt, iron and copper, are an important class of OER catalysts due to their abundant reserves and strong corrosion resistance. Among them, nickel oxide is considered to be a potential IrO2 catalyst because of its advantages such as harmlessness, low cost, strong corrosion resistance and high catalytic activity. 2 and RuO 2 However, in the process of water electrolysis, the active site Ni of nickel oxide is unstable, resulting in low catalytic activity. The introduction of doping atoms is beneficial to stabilize the active site. (ZWGao, JYLiu, XMChen, XLZheng, J.Mao, H.Liu, T.Ma, L.Li, WCWang, XWDu, Adv.Mater.31(2019)1804769; R.Ji, F.Zhang, Y.Liu, Y.Pan, Z.Li, Z.Liu, S.Lu, Y.Wang, H.Dong, P.Liu, X.Wu, H.Jin, Nanoscale 11(2019)22734–22742; L.Peng, J.Shen, X.Zheng, R.Xiang, M.Deng, Z.Mao, Z.Feng, L.Zhang, L.Li, Z.Wei, J.Catal.369(2019)345–351.) In addition, the electrical conductivity of nickel oxide is low, which affects its further application. Therefore, improving the electrical conductivity and stabilizing the active sites of nickel oxide materials is of great significance for hydrogen production by water electrolysis. Summary of the invention
[0003] In view of the technical problems existing in the prior art, the primary purpose of the present invention is to provide a doped nickel oxide-based material, in which the doped foreign atoms can change the electronic and structural properties of nickel oxide, thereby stabilizing the active sites and improving the electrical conductivity of the material, so that the doped nickel oxide-based material can efficiently electrocatalyze water to generate oxygen under alkaline conditions.
[0004] In order to achieve the above object, the present invention provides a method for preparing a doped nickel oxide-based material, comprising the following steps:
[0005] Nickel nitrate and ferric nitrate are added to an ethanol solution as a nickel source and an iron source, respectively. After being fully stirred, a mixed solution of ethanol and oleylamine is quickly added. After being fully stirred again, the solution is transferred to a reactor and heated for reaction. Subsequently, it is centrifuged and rinsed, and then calcined to obtain a precursor powder. The powder and thiourea are placed in a tubular furnace and heated to obtain a doped nickel oxide-based material.
[0006] Furthermore, in the above steps, the mass ratio of the nickel source to the iron source is 23:1 to 25:1.
[0007] Furthermore, in the above steps, the volume ratio of ethanol and oleylamine in the mixed solution is 4:1 to 6:1.
[0008] Furthermore, in the above steps, the heating temperature in the reaction kettle is 170 to 180°C.
[0009] Furthermore, in the above steps, the calcination temperature is 350 to 400°C.
[0010] Furthermore, in the above steps, the mass ratio of the precursor powder to thiourea is 1:10 to 1:8.
[0011] Furthermore, in the above steps, the temperature in the tube furnace is 350 to 400°C.
[0012] The present invention also provides an application of a doped nickel oxide-based material, characterized in that it is applied to an anode material for alkaline water electrolysis, and the steps are as follows:
[0013] 5 mg of the doped nickel oxide-based material was ultrasonically treated with a mixed solution of 1000 μL of deionized water, 200 μL of ethanol, and 5 μL of Nafion, and then 200 μL of the resulting mixture was coated on a glassy carbon electrode as an anode material.
[0014] Furthermore, the mixed solution is treated with ultrasound for 40 minutes.
[0015] Compared with the prior art, the present invention exhibits the following significant and beneficial effects, which together highlight the technological breakthrough and significant progress of the present invention in the relevant field.
[0016] (1) The present invention achieves better optimization in terms of synthesis method. Traditional synthesis technology often requires harsh reaction conditions, such as high temperature or specific precious metal catalysts, which not only increases production costs, but also may cause environmental pollution and safety hazards. The synthesis method of the present invention cleverly avoids these drawbacks. Its reaction conditions are mild, the operation is simple, and no complicated equipment and precious metals are required, which greatly reduces the difficulty and cost of production. This innovation not only improves production efficiency, but also makes the entire production process more environmentally friendly and safe, which is in line with the current development trend of green chemistry.
[0017] (2) From the perspective of material properties, the present invention cleverly introduces metallic iron and non-metallic sulfur atoms into the nickel oxide system through a carefully designed doping strategy. This innovative move has profoundly changed the electronic structure and physical properties of nickel oxide, especially significantly improved the stability of active sites and the electrical conductivity of the system. The improvement in electrical conductivity means that the material can reduce energy loss and improve energy conversion efficiency during current transmission, which is crucial for electrochemical applications. Therefore, the nickel oxide-based material of the present invention has broader application prospects in the fields of electrochemical energy storage, conversion, and catalysis.
[0018] (3) The doped nickel oxide-based material prepared by the present invention exhibits excellent water electrolysis performance under alkaline conditions. Traditional water electrolysis materials are often limited to the pH range, while the material of the present invention can work efficiently and stably in an alkaline environment. This feature gives it a unique advantage in the field of alkaline water electrolysis and hydrogen production. As an anode material, it can effectively promote the oxidation reaction of water molecules and improve the electrolysis efficiency, while maintaining good stability and durability, reducing the maintenance cost during long-term operation.
[0019] (4) The synthesis method of the present invention not only simplifies the production process and reduces costs, but also significantly improves the conductivity and water electrolysis performance of the material through the doping strategy, thereby achieving significant technological progress in the field of electrochemistry. These advantages make the present invention show great potential and value in alkaline water electrolysis hydrogen production, electrochemical energy storage and other related applications, and make important contributions to promoting the development and application of clean energy technology. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 This is a schematic diagram of the steps for synthesizing a doped nickel oxide-based material according to Example 1 of the present invention;
[0021] Figure 2 This is a schematic diagram of the microstructure of the synthesized doped nickel oxide-based material according to Example 1 of the present invention. DETAILED DESCRIPTION
[0022] Next, the technical solutions in the embodiments of the present invention will be clearly and completely described in conjunction with the drawings of the present invention. The described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, other embodiments obtained by ordinary technicians in this field without creative work are all within the scope of protection of the present invention. The experimental methods described in the following embodiments are all conventional methods unless otherwise specified; the reagents and materials, unless otherwise specified, can be obtained from public commercial channels.
[0023] In an embodiment of the present invention, a method for preparing a doped nickel oxide-based material comprises the following steps:
[0024] Nickel nitrate and ferric nitrate are added to an ethanol solution as a nickel source and an iron source, respectively. After being fully stirred, a mixed solution of ethanol and oleylamine is quickly added. After being fully stirred again, the solution is transferred to a reactor and heated for reaction. Subsequently, it is centrifuged and rinsed, and then calcined to obtain a precursor powder. The powder and thiourea are placed in a tubular furnace and heated to obtain a doped nickel oxide-based material.
[0025] In the above steps, the mass ratio of the nickel source to the iron source is 23:1 to 25:1.
[0026] In the above steps, the volume ratio of ethanol and oleylamine in the mixed solution is 4:1 to 6:1.
[0027] In the above steps, the heating temperature in the reaction kettle is 170 to 180°C.
[0028] In the above steps, the calcination temperature is 350 to 400°C.
[0029] In the above steps, the mass ratio of the precursor powder to thiourea is 1:10 to 1:8.
[0030] In the above steps, the temperature in the tube furnace is 350 to 400°C.
[0031] Technical principle of the present invention:
[0032] The subtlety of the method for preparing doped nickel oxide-based materials of the present invention lies in that a significant improvement in material performance is achieved by precisely controlling the raw material ratio and process steps. This process not only embodies the art of chemical synthesis, but also profoundly reveals the mystery of the synergistic effect between raw materials.
[0033] First, nickel nitrate and ferric nitrate are selected as nickel and iron sources, respectively, based on their high solubility in aqueous solution and easily controllable chemical properties. Nickel nitrate provides the nickel element required for the preparation of nickel oxide, while the addition of ferric nitrate is intended to achieve the doping of iron elements to adjust and optimize the electrical, magnetic or catalytic properties of the final material. The mass ratio of the nickel source to the iron source is precisely controlled between 23:1 and 25:1. The selection of this ratio range is crucial, as it directly affects the doping effect and the overall performance of the material. Too high or too low an iron content may cause the material performance to deviate from expectations, so strict control of this ratio is the key to obtaining an ideal doping effect.
[0034] Next, the two nitrates are dissolved in an ethanol solution. Ethanol as a solvent not only helps to evenly disperse the raw materials, but also promotes intermolecular contact in subsequent reactions. Then a mixed solution of ethanol and oleylamine is quickly added, in which the volume ratio of ethanol to oleylamine is carefully set to 4:1 to 6:1. Oleylamine, as a surfactant, plays a role in stabilizing the solution, preventing agglomeration, and promoting the formation of specific morphologies. This step is performed quickly to avoid possible side reactions in the solution and ensure effective mixing of the raw materials.
[0035] After the solution is evenly mixed, it is transferred to a reactor for heating reaction, and the heating temperature is set between 170 and 180°C. This temperature range is based on considerations of reaction kinetics and thermodynamic equilibrium, which can not only ensure the reaction rate, but also avoid side reactions or damage to the material structure caused by excessively high temperatures. During the reaction, nickel ions and iron ions undergo complex chemical reactions under the combined action of ethanol and oleylamine, and are gradually transformed into precursor structures.
[0036] After the reaction is completed, unreacted impurities and solvents are removed by centrifugal analysis, followed by a detailed rinsing step to ensure the purity of the precursor. Next, the precursor powder is placed in a calcining furnace and calcined at a temperature of 350 to 400°C. This step is intended to remove organic residues and promote the conversion of the precursor to nickel oxide-based materials while maintaining the microstructure of the material and the uniform distribution of doping elements. Precise control of the calcination temperature is critical to obtaining doped nickel oxide-based materials with high crystallinity, good stability and excellent performance.
[0037] Finally, the calcined powder is mixed with thiourea in a mass ratio of 1:10 to 1:8 and placed in a tube furnace and heated to 350 to 400°C. Thiourea is used as a sulfur source to further modify the surface properties of the material or introduce specific sulfur effects, such as enhancing catalytic activity or changing the electronic structure. The heating process in the tube furnace promotes the full reaction of sulfur with the precursor powder and achieves deep doping. The temperature control of this step is also strict to ensure the effective introduction of sulfur without destroying the main structure of the material.
[0038] It is worth noting that in the entire preparation process, the order of each step has been carefully designed and cannot be changed at will. Precise control of the amount of raw materials, careful adjustment of reaction conditions and optimization of process parameters are all indispensable for achieving high performance of materials. Any omission in any step or slight deviation in parameters may have a significant impact on the performance of the final material. Therefore, the success of this preparation method depends not only on the selection of raw materials, but also on the precise control of each step and the in-depth optimization of process parameters. These efforts have jointly contributed to the significant improvement of the performance of doped nickel oxide-based materials and achieved unexpected technical effects.
[0039] In order to make the disclosure of the present invention more complete, it is described below through more specific embodiments.
[0040] Example 1
[0041] A method for preparing a doped nickel oxide-based material, the preparation schematic diagram is as follows Figure 1 As shown, the specific preparation steps are as follows:
[0042] 0.314 g of nickel nitrate and 0.013 g of ferric nitrate were added as nickel source and iron source to 25 ml of ethanol solution, respectively. After being fully stirred for 30 minutes, a mixed solution of 9 ml of ethanol and 2 ml of oleylamine was quickly added. After being fully stirred again for 1 hour, the solution was transferred to a reactor and heated at 180°C for 24 hours. After cooling to room temperature, it was centrifuged and rinsed with ultrapure water and ethanol several times, and then calcined at 360°C for 3 hours to obtain a precursor powder. The powder and thiourea with a mass ratio of 1:10 were placed in porcelain boats on the downstream and upstream sides of the tube furnace, respectively. The temperature was raised to 350°C at a heating rate of 2 degrees Celsius per minute and maintained for 2 hours to obtain a doped nickel oxide-based material. The microstructure diagram is shown in FIG. Figure 2 shown.
[0043] The doped nickel oxide-based material obtained in this embodiment can be applied to the anode material of alkaline water electrolysis, and the steps are as follows:
[0044] A mixed solution of 5 mg of doped nickel oxide-based material and 1000 μl of deionized water, 200 μl of ethanol and 5 μl of Nafion was ultrasonicated for 40 minutes, and then 200 μl of the obtained mixture was coated on a glassy carbon electrode as an anode material. The catalytic activity of the doped nickel oxide-based material was tested using a Shanghai Chenhua CHI760E electrochemical workstation. A three-electrode system was used, with a Pt mesh as the counter electrode, a saturated calomel electrode as the reference electrode, and a 1 M KOH solution as the electrolyte. The current density was 10 mA / cm 2The overpotential of the system was measured to be 220 mV. Under constant current conditions, the anode material can work for 480 hours with a potential drop rate of less than 7%. The above results show that the doped nickel oxide-based material has high catalytic activity and stability as an anode material for alkaline water electrolysis.
[0045] Example 2
[0046] In this embodiment, a nickel oxide-based material doped only with iron is prepared, and the specific preparation steps are as follows:
[0047] 0.314 g of nickel nitrate and 0.013 g of ferric nitrate were added as nickel source and iron source to 25 ml of ethanol solution respectively. After being fully stirred for 30 minutes, a mixed solution of 9 ml of ethanol and 2 ml of oleylamine was quickly added. After being fully stirred again for 1 hour, the solution was transferred to a reactor, heated at 180°C for 24 hours, cooled to room temperature, centrifuged and rinsed with ultrapure water and ethanol several times, and then calcined at 360°C for 3 hours to obtain a nickel oxide-based material doped only with iron.
[0048] The iron-doped nickel oxide-based material obtained in this example was applied to the anode material of alkaline water electrolysis, and the steps were consistent with those in Example 1. The overpotential of the system was measured to be 276 mV, and the potential drop rate was less than 7% after working for 480 hours under constant current conditions.
[0049] Comparative Example 1
[0050] In this comparative example, commercial iridium oxide was used as the anode material for alkaline water electrolysis. The catalytic performance and stability performance of the test system were consistent with those in Example 1. The results showed that under the same test conditions, the higher overpotential of commercial iridium oxide indicated that its water electrolysis activity was lower than that of the doped nickel oxide-based material.
[0051] Although the present invention is disclosed as above, the implementation methods of the present invention are not limited to the above-mentioned embodiments, and any other changes, modifications, substitutions, combinations, and simplifications made without departing from the spirit and principle of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A method for preparing a doped nickel oxide-based material, characterized in that: The following steps are involved: Nickel nitrate and ferric nitrate are added to an ethanol solution as a nickel source and an iron source, respectively. After being fully stirred, a mixed solution of ethanol and oleylamine is quickly added. After being fully stirred again, the solution is transferred to a reactor and heated for reaction. Subsequently, the solution is centrifuged and rinsed, and then calcined to obtain a precursor powder. The powder and thiourea are placed in a tubular furnace and heated to obtain a doped nickel oxide-based material.
2. The method for preparing the doped nickel oxide-based material according to claim 1, characterized in that: The mass ratio of the nickel source to the iron source is 23:1 to 25:
1.
3. The method for preparing the doped nickel oxide-based material according to claim 1, characterized in that: The volume ratio of ethanol to oleylamine in the mixed solution is 4:1 to 6:
1.
4. The method for preparing the doped nickel oxide-based material according to claim 1, characterized in that: The heating temperature in the reactor was 170 to 180°C.
5. The method for preparing the doped nickel oxide-based material according to claim 1, characterized in that: The calcination temperature is 350 to 400°C.
6. The method for preparing the doped nickel oxide-based material according to claim 1, characterized in that: The mass ratio of the precursor powder to thiourea is 1:10 to 1:
8.
7. The method for preparing the doped nickel oxide-based material according to claim 1, characterized in that: The temperature in the tube furnace is 350 to 400°C.
8. A doped nickel oxide-based material prepared according to the method according to any one of claims 1 to 7.
9. An application of the doped nickel oxide-based material according to claim 8, characterized in that: Applied to the anode material of alkaline water electrolysis, the steps are as follows: 5 mg of the doped nickel oxide-based material was ultrasonically treated with a mixed solution of 1000 μL of deionized water, 200 μL of ethanol, and 5 μL of Nafion, and then 200 μL of the resulting mixture was coated on a glassy carbon electrode as an anode material.
10. The use of the doped nickel oxide-based material according to claim 9, characterized in that: The mixed solution was subjected to ultrasonic treatment for 40 minutes.